Npas3 regulates stemness maintenance of radial glial cells and neuronal migration in the developing mouse cerebral cortex - Liu, Ji-Wei; Li, Han; Zhang, Yang (Frontiers in Cellular Neuroscience, 2022)
The neuronal PAS domain 3 (NPAS3) is a member of the basic helix-loop-helix PAS family of transcription factors and implicated in psychiatric and neurodevelopmental disorders. NPAS3 is robustly expressed in the cortical ventricle zone (VZ), a transient proliferative zone containing progenitor cells, mainly radial glial cells, destined to give rise to cortical excitatory neurons. However, the role of NPAS3 in the corticogenesis remains largely unknown. In this study, we knocked down Npas3 expression in the neural progenitor cells residing in the cortical VZ to investigate the role of Npas3 in the cerebral cortical development in mice. We demonstrated that Npas3 knockdown profoundly impaired neuronal radial migration and changed the laminar cell fate of the cells detained in the deep cortical layers. Furthermore, downregulation of Npas3 led to the stemness maintenance of radial glial cells and increased the proliferation rate of neural progenitor cells residing in VZ/subventricular zone (SVZ). These findings underline the function of Npas3 in the development of the cerebral cortex and may shed light on the etiology of NPAS3-related disorders.